Relationships between punch impact force and upper- and lower-body muscular strength and power in highly trained amateur boxers - Dunn, E.; Humberstone, C.; Franchini, E.; Iredale, K.; Blazevich, A. (The Journal of Strength and Conditioning Research, 2020)
It is a given that punching power is one of the most important characteristics in striking combat sports. Despite a large focus on strength and power development in many athletes as a means to improve punching power, there isn`t a large amount of research showing the effectiveness of such training interventions, or even correlations between independent measures of strength and power, and punching force in combat athletes. As such, much of what drives our approach towards strength and conditioning for combat athletes originates from interpretation of studies related to biomechanically similar sports, combined with an application of basic kinesiology and sports performance principles.